2012
DOI: 10.1155/2012/510179
|View full text |Cite
|
Sign up to set email alerts
|

Acute Renal Failure Secondary to Tuberculosis: A Diagnostic Challenge

Abstract: Tuberculosis is a multiorgan disease with varied clinical presentations and is reemerging due to increasing immigration and globalization. We present the case of an immigrant female patient who developed acute renal failure with clinical and biochemical features suggestive of lupus nephritis but with a timely renal biopsy showing caseating granulomata in the renal parenchyma consistent with renal tuberculosis. Despite treatment with antituberculosis treatment and resolution of TB on repeat renal biopsy, she re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
2
1
Order By: Relevance
“…18 Nephrotic syndrome in LN is usually non-simple and combined with hematuria and even renal failure. 19 The current study found no significant differences in IgG, IgA, and IgM levels between patients with LN with and without renal damage, and between patients with mild and severe LN. However, the mean immunoglobulin levels were lower in patients with LN with renal damage and in patients with severe LN.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…18 Nephrotic syndrome in LN is usually non-simple and combined with hematuria and even renal failure. 19 The current study found no significant differences in IgG, IgA, and IgM levels between patients with LN with and without renal damage, and between patients with mild and severe LN. However, the mean immunoglobulin levels were lower in patients with LN with renal damage and in patients with severe LN.…”
Section: Discussioncontrasting
confidence: 74%
“…18 Nephrotic syndrome in LN is usually non-simple and combined with hematuria and even renal failure. 19…”
Section: Discussionmentioning
confidence: 99%
“…Urine TB culture performed poorly, which has been noted previously . In one study of TB‐GIN, urine culture for Mycobacterium tuberculosis had a yield of 25% . All patients in our cohort with positive urine cultures for TB, and/or AFBs observed on the kidney biopsy, had microbiological evidence of TB elsewhere.…”
Section: Discussionmentioning
confidence: 99%